Stability of viral haemorrhagic septicaemia virus, infectious hematopoietic necrosis virus and cyprinid herpesvirus 3 in various water samples - Ullrich, Johanna; Christian, Juergen; Bergmann, Sven Michael; Oberle, Martin; Becker, Anna (Journal of Fish Diseases, 2020)
Rainbow trout (Oncorhynchus mykiss) and common carp (Cyprinus carpio) are the two most common species in traditional fish farming in Germany. Their aquaculture is threatened upon others by viruses that can cause a high mortality. Therefore, this work focuses on three viruses-viral haemorrhagic septicaemia virus, infectious hematopoietic necrosis virus and cyprinid herpesvirus 3 (CyHV-3)-that endanger these species. To prevent their spread and contain further outbreaks, it is essential to know how long they can outlast in environmental waters and what affects their infectivity outside the host. Hence, the stability of the target viruses in various water matrices was examined and compared in this work. In general, all three viruses were quite stable within sterile water samples (showing mostly <= 1 log reduction after 96 hr) but were inactivated faster and to a higher extent (up to five log steps within 96 hr) in unsterile environmental water samples. The inactivation of the viruses correlated well with the increasing bacterial load of the samples, suggesting that bacteria had the greatest effect on their stability in the examined samples. In comparison, CyHV-3 seemed to be the most sensitive and maintained its infectivity for the shortest period.
CRIS-Team WoS Importer:2021-01-01